1981
DOI: 10.1161/01.cir.64.6.1191
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic duplex scanning for disease of the carotid artery.

Abstract: The duplex ultrasonic scanner combines real-time B-mode imaging with a single-gate, variable-range pulsed Doppler. The detection and categorization of the severity of carotid artery atherosclerosis is achieved by performing spectral analysis of the pulsed Doppler velocity signal obtained from vessels of interest. Using this technique, 750 patients with suspected extracranial carotid artery disease were evaluated between January 1978 and January 1980. One hundred thirty-five of these 750 patients (18%) underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
1
3

Year Published

1982
1982
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 204 publications
(46 citation statements)
references
References 8 publications
3
39
1
3
Order By: Relevance
“…The main problems are the investigation of the proximal part of the vertebral artery and the differentiation of severe stenosis, occlusion, hypoplasia and aplasia (von Reutern et al, 1976, Hennerici et al, 1981. Ultrasonic duplex scanning with spectral analysis of the Doppler signal is a very reliable technique for the detection of carotid atherosclerosis (Fell et al, 1981;Breslau, 1982;Ackerstaff et al, 1982). To date no reports are available about the accuracy of duplex ultrasound scanning of the innominate, subclavian and vertebral arteries.…”
Section: Discussionmentioning
confidence: 99%
“…The main problems are the investigation of the proximal part of the vertebral artery and the differentiation of severe stenosis, occlusion, hypoplasia and aplasia (von Reutern et al, 1976, Hennerici et al, 1981. Ultrasonic duplex scanning with spectral analysis of the Doppler signal is a very reliable technique for the detection of carotid atherosclerosis (Fell et al, 1981;Breslau, 1982;Ackerstaff et al, 1982). To date no reports are available about the accuracy of duplex ultrasound scanning of the innominate, subclavian and vertebral arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that an increase in spectral broadening during systole without a concomitant increase in peak systolic frequency is a useful feature to predict disease states of <50% diameter reduction by arteriography. 2 Peak systolic flow velocities of > 120 cm/sec in the proximal ICA correlate well with disease of >50% diameter reduction. This threshold value was empirically obtained using a 5-MHz ultrasound duplex system at a Doppler angle of 60°i n the proximal ICA while assuming an axial direction for the flow velocity vector.…”
mentioning
confidence: 94%
“…39 The variables for classifying the degree of stenosis into these groups depend upon the recorded peak frequencies from the diseased area as well as the time of onset and degree of spectral broadening. After several validation studies, we decided to use the spectral criteria shown in Table 1.…”
Section: Direct Testsmentioning
confidence: 99%